Sound reproduction levels in portable players used by pupils in Warsaw secondary schools - Rogowski, P.; Rościszewska, T.; Jaroszewski, A. (Archives of Acoustics, 2001)
Sound pressure levels in insert headphones used by young users of CC and CD players were measured in 421 cases. In 137 of these cases short selections of music were recorded and analysed. The results show SPLs in excess of what is considered as a safe sound pressure level.